Flood Detection Control System Design Based on SMS Gateway - Iqbal Kamil Siregar; Jhonson Efendi Hutagalung; Bachtiar Efendi; Herman Saputra (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Flood concern everybody in every flood area. It makes the researchers interest to take the research about flood detection system, especially in rivers by using mobile phone facilities. The procedure of this tool is if the flood rise due to overflow of the river, then the river guard will receive SMS to tell the people to anticipate the flood by sounding the alarm until the entire riverbank area. This SMS delivery is via connection to telecommunications network using SMS gateway module. This tool can be used as a flood emergency which is installed at river location points where sensors and control devices are permanently installed. This research has been successful and has been well tested in its implementation.